MUTU DALAM LEMBAGA PENDIDIKAN ISLAM - Zulfakar, Zulfakar (Jurnal Visionary : Penelitian dan Pengembangan dibidang Administrasi Pendidikan, 2019)
Abstract: Management is a theory that is used as a foundation to carry out all organizational activities which have been jointly determined, in order to achieve togetherness of vision and mission in institutions, of educational institutions in particular, both in the domain of national and institutional objectives. Improving the quality of education becomes a very urgent problem, related to customers, from direct education users